Crystal structure of the OH‐dominant gadolinite‐(Y) analogue (Y, Ca)2(Fe, □)Be2Si2O8(OH, O)2 from Heftetjern pegmatite, Norway. Issue 5 (20th September 2017) - Chukanov, Nikita V.; Aksenov, Sergey M.; Rastsvetaeva, Ramiza K.; Kristiansen, Roy; Pekov, Igor V.; Belakovskiy, Dmitriy I.; Van, Konstantin V.; Bychkova, Yana V.; Britvin, Sergey N.
Abstract : A hydroxyl‐dominant analogue of gadolinite‐(Y) has been discovered in the Heftetjern granitic pegmatite, southern Norway. Data are provided here on the chemical composition, physical properties and crystal structure of this mineral, as well as its relationships with other members of the gadolinite–datolite group. Abstract : A hydroxyl‐dominant analogue of gadolinite‐(Y) (OH‐Gad) has been discovered in the Heftetjern granitic pegmatite, southern Norway, in association with late‐stage rare‐earth‐element containing minerals. The empirical formula, based on ten O atoms per formula unit, is (Y1.285 Ca0.55 Ce0.07 La0.04 Nd0.01 )Σ1.955 (Fe 2+ 0.57 □0.43 )Be2.02 Si1.995 O8.48 (OH)1.52 . The mineral is monoclinic, space group P 21 / c, a = 4.7514 (10), b = 7.5719 (16), c = 9.9414 (2) Å, β = 90.015 (4)°, V = 357.663 (3) Å 3 and Z = 2. The density calculated using the empirical formula is 3.903 g cm −3 . The crystal structure was refined to R = 0.0217 for 776 reflections with I > 2σ( I ). OH‐Gad is isostructural with gadolinite‐(Y) and it is characterized by the predominance of OH − over O 2− at the anionic Ø‐site. The refined crystal‐chemical formula is: A (Y1.25 Ca0.55 Ce0.2 ) X (Fe 2+ 0.57 □0.43 ) Z Be2 T Si2 O8 Ø [(OH)0.86 O0.59 (OH)*0.55 ] ( Z = 2). The possible orientation and local environment of the hydroxyl group were suggested based on bond‐valence sum calculations and geometrical analysis of the crystal structure. The infrared spectrum confirms disordering of H atoms. OH‐Gad seems to be a potentially new mineral, the first simultaneously hydroxyl‐ and iron‐dominant member of the gadolinite subgroup. It is an OH‐analogue of gadolinite‐(Y) and an Fe 2+ ‐analogue of hingganite‐(Y).